PERSEPSI ANTARA TENAGA KERJA PENDATANG LAKI-LAKI DAN PEREMPUAN TERHADAP PUSH AND PULL FACTORS - Septiani Riwanti; Dwi Kartikasari (Politeknik Negeri Batam, 2019)
This research is aimed to know the difference of perception between National Migrant Workers of Men And Women Against Push And Pull Factors. The variable of push factors used in this research is that of job field, low wage, seeking capital and necessity of life. And pull factors are job opportunities, high wages, distance and culture. Then the data is processed using SPSS 20 software with parametric metode that is independent sample t test. The result of the research revealed that there is no difference of perception between men and women on the job field (push factor), there is no difference of perception between men and women to low wages (push factor), there is no difference of perception between men and women against looking for capital (push factor), there are differences of perceptions between men and women on the necessity of life (push factor), there are differences of perceptions between man and woman to job opportunity (pull factor), there are differences of perceptions between men (pull factor), there are differences in perceptions between men and women on the distance factor (pull factor) and there are differences in perceptions between men and women to the pull factor